2009
DOI: 10.1158/0008-5472.can-08-4546
|View full text |Cite
|
Sign up to set email alerts
|

HOXA13 Promotes Cancer Cell Growth and Predicts Poor Survival of Patients with Esophageal Squamous Cell Carcinoma

Abstract: Homeobox genes are known to be classic examples of the intimate relationship between embryogenesis and tumorigenesis. Here, we investigated whether inhibition of HOXA13, a member of the homeobox genes, was sufficient to affect the proliferation of esophageal cancer cells in vitro and in vivo, and studied the association between HOXA13 expression and survival of patients with esophageal squamous cell carcinoma (ESCC). HOXA13 expression was permanently knocked down using an RNA interference technique, and cell s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…As a transcription factor, immunohistochemical labeling for HOXA13 is expected to localize in nuclei of HCC cells, as previously reported (Knosp et al 2004;Cillo et al 2011). However, Gu et al (2009) also found cytoplasmic localization of HOXA13 in esophageal squamous cell carcinoma and this phenomenon was also found in many other transcription factors (Sun et al 2013). The regulation of transcription factor activity plays an important role in many biological processes.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As a transcription factor, immunohistochemical labeling for HOXA13 is expected to localize in nuclei of HCC cells, as previously reported (Knosp et al 2004;Cillo et al 2011). However, Gu et al (2009) also found cytoplasmic localization of HOXA13 in esophageal squamous cell carcinoma and this phenomenon was also found in many other transcription factors (Sun et al 2013). The regulation of transcription factor activity plays an important role in many biological processes.…”
Section: Discussionmentioning
confidence: 84%
“…Available evidence indicates that HOXA13 plays a prominent role in tumor survival and progression (Gu et al 2009;Cillo et al 2011). In embryonic development, each HOX gene is expressed in a spatiotemporal pattern, and thus HOXA13 is expressed specifically in the cloacal mesoderm and hindgut, but not in liver Roberts et al 1995;Takahashi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Here, we show that HCC selection on the basis of HOXA13 hyperexpression correlates, at transcriptome level, with the identification of expression gene profiles characteristic of liver development/cell cycle/nuclear pore related HCC phenotypes displaying poor prognosis.…”
mentioning
confidence: 82%
“…The expression of HOX genes keeps to temporal and spatial colinearity in embryonic development (Shah and Sukumar, 2010). Aberrant expression of HOX genes was found in various types of cancer, such as ovarian cancer (Yamashita et al, 2006), leukemia (Chang et al, 1997), breast cancer (Jin et al, 2012), cervical cancer (How et al, 2013), prostate cancer (Rubin et al, 2007), melanoma (Care et al, 1996), oral squamous cell cancer (De Souza Setubal Destro et al, 2010) and esophageal squamous cell cancer (Gu et al, 2009). However, the detailed relationship between HOX genes and tumorigenesis remains unclear (Shah and Sukumar, 2010).…”
Section: Hoxb7 Predicts Poor Clinical Outcome In Patients With Advancmentioning
confidence: 99%